A survey of biosecurity practices of pig farmers in selected districts affected by African swine fever in Uganda - Ekakoro, John E.; Nawatti, Margaret; Singler, David F.; Ochoa, Krista; Kizza, Robinah; Ndoboli, Dickson; Ndumu, Deo B.; Wampande, Eddie M.; Havas, Karyn A. (Frontiers in Veterinary Science, 2023)
Introduction In Uganda, pig production is an important source of livelihood for many people and contributes to food security. African swine fever (ASF) is a major constraint to pig production in Uganda, threatening the food supply and sustainable livelihoods. Prevention of ASF primarily relies on good biosecurity practices along the pig value chain. Previous studies showed that biosecurity along the pig value chain and on farms in Uganda is poor. However, the biosecurity practices of pig farmers in ASF affected areas of Uganda and their opinions on on-farm ASF morbidity and mortality were previously not comprehensively characterized. The objectives of this study were to document pig farmers’ experiences with ASF in their farms and to describe the pig biosecurity practices in districts of Uganda that were highly affected by ASF. Methods A total of 99 farmers were interviewed in five districts. Data were collected by way of triangulation through farmer interviews, field observations during the farmer interviews, and a survey of key informants. However, farmer interviews were considered the primary source of data for this study. Farmers’ biosecurity practices were scored using a biosecurity scoring algorithm. Results Forty-one out of 96 (42.7%) farmers reported having pigs with ASF in the past 12 months. The level of pig farming experience (p = 0.0083) and herd size (p < 0.0001) were significantly associated with the reported occurrence of ASF. Overall, the biosecurity scores for the respondents were considered poor with 99% (98/99) scoring <70% and just one farmer obtaining a fair score of 72.2%. District (p = 0.0481), type of husbandry system (p = 0.014), and type of pig breed raised (p = 0.004) were significantly associated with farmer’s biosecurity score. Conclusion Continued farmer education on ASF and the importance of good biosecurity practices is necessary. More in-depth scientific inquiry into the factors influencing the biosecurity practices among pig farmers in Uganda is necessary.